Freedom, dignity and happiness: a look from Enrique Dussel's philosophy in the era of artificial intelligence - Oswaldo Jesús Martínez-Padrón; Milda Margarita Rangel-Velasco (Dialogos, 2025)
Freedom and dignity have been fundamental to human development, being vital to the pursuit of happiness. In this context, we explore how Artificial Intelligence maintains a dual role: while it can be a powerful tool for inclusion and equity, it can also perpetuate inequalities, if not properly managed. From there, it is interesting to take a look at the postulates of Dussel's philosophy of happiness, concluding that its ethical use can contribute to decolonization, promote global equity and outline the realization of happiness, generally mutilated by oppressive dynamics.